Changes of the enterprise characteristics of spatial economic structure in the north-hungarian region - Balla, G. (НТУ "ХПІ", 2012)
In this publication I analysed the tendency of the number of people employed by enterprises that operate in the counties of the North-Hungarian region and the development of the GDP produced by such enterprises according to consolidated national economic sectors. On the basis of the analysis it can be stated that in the North-Hungarianregion, and also in Hungary as a whole, the share ofthe manufacturing industry decreased, while the share of the tertiary industry increased. As the result of this, the possibility of the economic instability in-creased, because the role of industries that ensure the stability, primarily of those which are bound to place and capital equipment, diminished and the role of the easy-to-mobilise tertiary industry appreciated. Thus, on the long term the region's economic development can only be ensured by means of economic development policy inciting continuous investments.
Keywords: spatial economic structure; GDP; employed; national economic sector; North-Hungary